Klasifikasi Coronary Heart Disease (CHD) Berbasis Optimasi DNN dan Inisialisasi Kaiming He - Lia Andiani; Sukemi Sukemi; Dian Palupi; Nurul Afifah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
CHD is chest pain or discomfort that occurs if the area of the heart muscle does not get enough oxygen-rich blood. CHD is also known as coronary artery disease. CHD is increasing every year with a significant number of deaths. A learning algorithm is proposed to get better performance in accuracy, sensitivity, and specificity in CHD interpretation. Accuracy can be improved by adding a Kaiming He (2015) weight initialization optimization technique to the DNN structure. Therefore we propose that DNN is optimized with a Kaiming He weight initialization technique so that it can overcome weaknesses in the data variant. This is evidenced by the results of the accuracy performance of 98.73%. Initialization of kaiming he weights is proven to improve accuracy and overcome the problem of large data variants between classes